Effect of perivitelline fluid from horseshoe crab on the expression of cell cycle regulatory genes in human dental pulp stem cells - Rani, Abdul Qawee; kannan, Thirumulu Ponnuraj; Azmi, Nur Izyan; Ibrahim, Najian; Omar, Nor Shamsuria; Ahmad, Azlina; Mokhtar@Makhtar, Khairani Idah (Universiti Sains Malaysia, 2016)
Abstract Perivitelline fluid (PVF) of the horseshoe crab embryo has been reported to possess an important role during embryogenesis by promoting cell proliferation. This study aims to evaluate the effect of PVF on the expression of cell cycle regulatory genes from human dental pulp stem cells (DPSCs) between different cell passages viz. 4, 5, 6. The cells were treated with a single dose of PVF (26.89 mg/ml) PVF. Gene expression was quantified for CDKNA2A, PTEN, MDM2 and TP53 genes using reverse transcriptase PCR. CDKN2A and MDM2 expression for treated and untreated DPSCs, expressed a similar pattern of expression. The higher expression of CDKN2A showed that the treatment increased cell proliferation and prevented cell senescence. DPSCs with PVF treatment showed increased expression of MDM2 at passage 4 and drastically declined expression at passage 5 and slightly increased at passage 6. TP53 expression of DPSCs treated group showed a higher expression compared to untreated group. On the other hand, the expression of PTEN in DPSCs treated group started to increase from passage 5 to 6. However, on the whole, the PTEN expression was higher than the untreated group in all the passages studied here. The results showed that PVF could enhance cell cycle regulatory gene expression in DPSCs as indicated by the higher expression of all the genes considered in this study at different cell passages in the treated group compared to the untreated group. Mann Whitney test was utilized to determine the significance of cell cycle regulatory genes expression between treated and untreated group. Significant difference in expression of genes between the treated and untreated groups were found at all passages except for CDKN2A gene whereby, its expression was not significantly different at passage 5 though it did express slightly higher in PVF treated DPSCs. Keywords: cell cycle, dental pulp stem cells, gene expression, horseshoe crab, perivitelline fluid.